2005
DOI: 10.1094/cc-82-0609
|View full text |Cite
|
Sign up to set email alerts
|

Application of Response Surface Methodology in the Development of Gluten‐Free Bread

Abstract: Cereal Chem. 82(5):609-615The formulation of gluten-free (GF) bread of high quality presents a formidable challenge as it is the gluten fraction of flour that is responsible for an extensible dough with good gas-holding properties and baked bread with good crumb structure. As the use of wheat starch in GF formulations remains a controversial issue, naturally GF ingredients were utilized in this study. Response surface methodology was used to optimize a GF bread formulation primarily based on rice flour, potato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
125
0
5

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(141 citation statements)
references
References 32 publications
11
125
0
5
Order By: Relevance
“…The improving effect of hydrocolloids on the bread volume has been reported by several authors [10,12,14,[41][42]. The addition of hydrocolloids (carboxymethylcellulose, agarose, xanthan, β-glucan, pectin) at 1% supplementation level produced an increase in the volume of gluten-free bread except for xanthan and pectin, although when the hydrocolloid dosage increased from 1% to 2% the opposite effect was observed, except for pectin [10].…”
Section: Effect Of the Different Ingredients And Processing Aid On Thmentioning
confidence: 61%
See 2 more Smart Citations
“…The improving effect of hydrocolloids on the bread volume has been reported by several authors [10,12,14,[41][42]. The addition of hydrocolloids (carboxymethylcellulose, agarose, xanthan, β-glucan, pectin) at 1% supplementation level produced an increase in the volume of gluten-free bread except for xanthan and pectin, although when the hydrocolloid dosage increased from 1% to 2% the opposite effect was observed, except for pectin [10].…”
Section: Effect Of the Different Ingredients And Processing Aid On Thmentioning
confidence: 61%
“…The addition of hydrocolloids (carboxymethylcellulose, agarose, xanthan, β-glucan, pectin) at 1% supplementation level produced an increase in the volume of gluten-free bread except for xanthan and pectin, although when the hydrocolloid dosage increased from 1% to 2% the opposite effect was observed, except for pectin [10]. McCarthy et al [14] also reported a slight decrease in the gluten-free bread volume when increasing the addition level of HPMC.…”
Section: Effect Of the Different Ingredients And Processing Aid On Thmentioning
confidence: 97%
See 1 more Smart Citation
“…As the germination time increased, the springiness value decreased, indicating an increase in fragility and tendency to crumble when is sliced (McCarthy et al 2005). Indeed, after 12 h of germination springiness values were lower than the ones reported before in gluten free rice bread (Marco and Rosell 2008;Matos and Rosell 2012).…”
Section: Evaluation Of Bread Qualitymentioning
confidence: 75%
“…This has been exhibited while playing with the ingredients of composite flours for bakery products by several researchers (McCarthy et al 2005;Mezaize et al 2009;Sabanis et al 2009;Chakraborty et al 2010;Demirkesen et al 2011). …”
Section: Introductionmentioning
confidence: 93%